Pengaruh Efektivitas Penggunaan SIA, Pelatihan SIA, dan LOC Internal Pada Kinerja Karyawan LPD Kota Denpasar - Pawitri, Ni Made Sri; Yenni Latrini, Made (E-Jurnal Akuntansi; Vol 27 No 3 (2019)DO - 10.24843/EJA.2019.v27.i03.p17, 2019)
Determination of the sample in this study using a sampling technique with nonprobability sampling method, especially the purposive sampling method. This research was conducted on all LPDs in Denpasar City. The number of samples taken were 35 LPDs with 105 observations. Data collection is done by questionnaire instrument. The results of this questionnaire were measured using a Likert scale. The data analysis technique used is multiple linear regression analysis. Based on the results of the study, it is known that the effectiveness variables of the use of SIA, SIA training, and internal LOC have a positive effect on the performance of LPD employees in Denpasar City. This shows that the use of SIA that is more effective, routine in conducting training accompanied by confidence in individual users will provide convenience and benefits for employees who have an influence on improving the performance of LPD employees in Denpasar City. Keywords: Effectiveness of the use of SIA, SIA training, Internal LOC, employee performance